Mood, behavior, testosterone, cortisol, and interleukin‐6 in adults during immune activation: A pilot study to assess sickness behaviors in humans. Issue 1 (22nd August 2014) - Shattuck, Eric C.; Muehlenbein, Michael P.
<x xml:space="preserve">Abstract</x> Objectives Sickness behavior, a suite of behavioral changes subsequent to infection that includes depression, decreased social behaviors, and sleep disturbances, has been well described in model organisms. The phenomenon is relatively unexplored in humans due to methodological difficulties, and hormonal correlates of sickness behavior have not been studied. We therefore attempted to use a vaccine to elicit sickness behaviors outside of a clinical setting and uncover any correlations among testosterone, cortisol, and sickness behavior. Methods Eleven participants (five male, six female, mean age 22.8 years) naïve to the rabies vaccine were recruited from the School of Veterinary Medicine at Purdue University. Participants provided daily saliva and urine samples and completed questionnaires to assess mood and social behaviors for a period of 6 weeks. Saliva samples were assayed for cortisol and testosterone. Urine samples were assayed for interleukin‐6 and creatinine. Results Analysis revealed an expected decrease in testosterone and an increase in cortisol. While mood did not differ, other behaviors, such as physical activity and hours slept, showed expected changes following vaccination. However, none of these results achieved statistical significance. Conclusion Our results, while generally confirming previous research on sickness behavior and hormone changes during infection, are suggestive, but not statistically significant and so neither confirm nor contradict our hypotheses. We attribute this lack of significance to both the small sample size, as well as possible confounding factors, including the psychosocial stress of entering an intensive study program. Am. J. Hum. Biol. 27:133–135, 2015. © 2014 Wiley Periodicals, Inc.